A modified phase-field three-dimensional model for droplet impact with solidification. (July 2019) - Shen, Mingguang; Li, Ben Q.; Yang, Qingzhen; Bai, Yu; Wang, Yu; Zhu, Shaochong; Zhao, Bin; Li, Tianqing; Hu, Yongbao
Highlights: The solution of the Cahn-Hilliard equation to track moving boundaries. A heat source term added in energy equation to trace solidification profile. Thermal contact resistance studied to find its effect on maximum spread factor. A supersonic impact of ceramic particles examined. Abstract: A modified phase-field three-dimensional model has been developed to simulate the spreading of an impacting droplet undergoing solidification. The model is based on the numerical solution of the Cahn-Hilliard equation coupled with the Navier-Stokes equations for fluid flow and the energy balance equation for heat transfer. The solidification profile is tracked by treating the latent heat as a source term in the energy equation, which is modified to work with the Cahn-Hilliard equation. To verify the model, five cases were tested and matched well with experiments. Also, the effect of thermal contact resistance on the maximum spread factor of a solidifying droplet is discussed. One case was taken from practical thermal spraying conditions where a solidifying ceramic droplet spreads on a cold surface at a supersonic impact velocity; computed results are consistent with available measurements.